Possibilities of Therapeutic Angiogenesis in Patients with Critical Lower Limb Ischemia - I. P. Mikhailov; N. V. Borovkova; B. V. Kozlovsky; I. N. Ponomarev; N. Ye. Kudryashova; O. V. Leshchinskaya (Неотложная медицинская помощь)
Two clinical observations of effective treatment of patients with critical ischemia of the lower extremities using plasma-free lysate autologous platelets. Both patients were male, 73 and 53 years old. Both were diagnosed with total damage to the arteries of the infrainguinal zone. One of them had previously undergone endarterectomy from the femoral artery with subsequent thrombosis. After examination and joint discussion with x-ray endovascular surgeons, they were found inoperable. Due to the ineffectiveness of standard conservative therapy, the patient was offered local administration of plasma-free lysate autologous platelets. After receiving written informed consent, the procedure for collecting venous blood and obtaining plasma-free lysate autologous platelets and the introduction of this drug into the muscles of the leg from the side of ischemia according to the original method. The method for assessing microcirculation was three-phase scintigraphy : before treatment, both patients showed a significant decrease in the inclusion of osteotropic radiopharmaceutical in the soft tissues of the legs. For areas of radiopharmaceutical hyperfixation, relative accumulation coefficients were calculated: for one patient, the calculation results demonstrated the formation of foci of aseptic necrosis. When patients were re-hospitalized after 6 months, there was an improvement in local status and relief of rest pain. According to scintigraphy, a significant improvement in microcirculation was noted; no foci of aseptic necrosis were identified. Thus,  the use of plasma-free lysate autologous platelets in combination with complex conservative therapy has demonstrated positive results; this method can be considered as an alternative revascularization ischemic limb.